PATHOGENESIS OF DEMYELINATING DISEASES IN TERMS OF ECOPATHOLOGY (World Science, 2023)
The experiment have been researched changes that may occur in the brains of people who worked or lived for a long time in an area of risk of permanent pollution  with non-toxic doses of lead, 20-30 years after leaving the area. It was revealed that in the brain of experimental animals the number of neurons is reduced, gliosis, proliferation of microglia, destruction of blood vessels are noted, and processes of demyelination of white matter occur. These changes are more or less pronounced in all areas of the brain, to a greater extent in animals that received lead in more quantities. The identified morphological changes in the brain suggest that lead is one of the causes of the pathogenesis of demyelinating diseases.